2003
DOI: 10.1046/j.1440-1746.2003.03011.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential, stage‐dependent expression of Hsp70, Hsp110 and Bcl‐2 in colorectal cancer

Abstract: Taken together, our study demonstrated for the first time a differential, stage-dependent expression of Hsp70, Hsp110 and Bcl-2 in CRC. We suggest that the molecular mechanisms underlying the differential expression of Hsp and Bcl-2 family members deserves a more rigorous future study, the results of which might offer novel modes of rationale and strategy to predict and manipulate the malignant progression of colorectal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 56 publications
8
69
0
2
Order By: Relevance
“…Only a few previous studies, which were conducted with small colorectal cancer sample sizes, reported that HSP110 overexpression was associated with worse overall survival, advanced stage and nodal metastasis in colorectal cancer. 36,37 In these circumstances, the study by Dorard et al 25 provided important clues about the effect of HSP110 mutations on colorectal cancer. It is reasonable that the increased expression of mutant HSP110 inhibits the normal functions of HSP, which are beneficial to cancer cell survival; therefore, this molecular alteration can result in positive effects on survival in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few previous studies, which were conducted with small colorectal cancer sample sizes, reported that HSP110 overexpression was associated with worse overall survival, advanced stage and nodal metastasis in colorectal cancer. 36,37 In these circumstances, the study by Dorard et al 25 provided important clues about the effect of HSP110 mutations on colorectal cancer. It is reasonable that the increased expression of mutant HSP110 inhibits the normal functions of HSP, which are beneficial to cancer cell survival; therefore, this molecular alteration can result in positive effects on survival in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of HSP70 has been shown as a marker for advanced disease and lymph node metastasis in colorectal carcinoma (Lazaris et al 1997;Hwang et al 2003), BC and undifferentiated ovarian cancer (Athanassiadou et al 1998). In cervical cancer, it is correlated with tumor size and increased proliferation (Ralhan and Kaur 1995).…”
Section: Al 2010)mentioning
confidence: 99%
“…Furthermore, there are a number of reports indicating that high expression of Hsp72 in human tumors, especially of epithelial origin, correlates with high invasiveness, metastasis, poor prognosis of the disease and resistance to chemotherapy (Ciocca et al, 1993;Costa et al, 1997;Vargasroig et al, 1997;Nanbu et al, 1998). For example, in colorectal and lung cancers, expression of Hsp72 closely correlates with advanced clinical stages and positive lymph node involvement (Volm et al, 2002;Hwang et al, 2003). These findings suggest that Hsp72 provides a selective advantage to tumor cells during cancer progression.…”
Section: Introductionmentioning
confidence: 99%